Vaccine attitudes and education of parents - Dońka, Katarzyna; Suwała, Marlena; Zarzycka, Danuta; Sobolewska-Samorek, Agnieszka; Paździor, Violetta (Nursing in the 21st Century, 2018)
VACCINE ATTITUDES AND EDUCATION OF PARENTSIntroduction. Currently in Poland there is significant differentiation of parents’ attitudes towards vaccinating children. As a consequence, the number of unvaccinated children grows steadily by about 40 percent each year.Aim. Getting to know parents’ attitudes and their causes in relation to immunization based on the analysis of publications on this topic.Material and methods. Selection of publications for analysis was based on criteria of systematic review covering the last 10 years, cataloged in the following databases: Polish Medical Library, Google Scholar and Pubmed. The base searches were carried out according to the key words: protective vaccinations, parents’ attitudes, implementation of the vaccination calendar, immunization, vaccination, parental refusal of vaccines. As many as 32 publications were used in the study.Results. Vaccine knowledge of parents determines their attitude towards vaccination, which influences the implementation of primary and extended vaccinations in children. Implementation of the Protective Vaccination Program remains high in Poland, but the number of parents who refuse to vaccinate their children is systematically growing. Among the many reasons for the refusal of vaccination in children, the most often in literature there were those indicated by barriers of a religious, personal and philosophical nature, security and knowledge on this subject.Conclusions. Low level of parents’ knowledge, both general and specific, about vaccinations is the most common barrier in the implementation of mandatory vaccinations.